Peran Serta Pengawas Sekolah dalam Meningkatkan Kualitas Pendidikan, Menyongsong Masyarakat Ekonomi Asean di Kota Lhokseumawe - Fauziah Fauziah (Universitas Negeri Medan, 2015)
In 2015 we have entered in a free trade system in the Southeast Asian region which is called frequently as ASEAN Economic Society (MEA). We have known that MEA aims to increase the economic stability in the ASEAN region and forming a strong economic area inter-ASEAN countries. By implementing MEA in the late of 2015, the member country of ASEAN will sell goods and services easily to the other countries throughout Southeast Asia so that this can effect to the very intensive competition. In this matter, the significant thing which should be done by the Indonesian government especially city government of Lhokseumawe in facing the MEA is by preparing the quality human resources to be compete in the regional and international level. For increasing the quality of human resources is through the educational instituion at least by increasing the role of school supervisor to oversee and control toward the educational process. Without supports of supervising of school, education will not work optimally because the school supervisors responsible in controlling and giving advices for educational achievements.